Impact of fertigation and drip system layout on performance of chilli(Capsicum annum) - Nadiya Nesthad (Department of Land and Water Resources and Conservation Engineering, Kelappaji College of Agricultural Engineering and Technology, 2012)
The study “Impact of fertigation and drip system layout on performance of Chilli (Capsicum annum)” was taken up with the objective of determining the effect of fertigation, drip system layout and different levels of irrigation for chilli under plastic mulch. Different fertigation equipments like ventury injector, dosmatic fertigation unit and fertilizer tank were tested to study the hydraulic performance of the system. Ventury injector for fertilizer application was found to have high suction rate in comparison with dosmatic fertigation unit. The suction rate and motive flow rate was found to vary directly with respect to the pressure drop between the inlet and outlet of the fertigation equipment. Ventury injector can be used only if the discharge rate is above 14.6 L/min. Dosmatic fertigatrion unit and fertilizer tank can be used if the discharge rate is above 1.1 L/min and 6.6 L/min. The moisture distribution pattern under different drip field layout was observed. The moisture content near to the plant base was found to be high and decreases as the distance from the emitters increased. The effect of different irrigation levels and drip system layout under plastic mulch on the performance of Chilli (Capsicum annum), Ujwala variety was also studied. The number of branches, stem girth and yield showed significant difference between the treatments. The yield showed significant difference with different levels of irrigation and drip system layout. Maximum yield of 18.32 t/ha was observed for the treatment T5. The treatments T6 (17.952 t/ha) was on par with the treatment T5. The benefit cost ratio for treatment T5, 85 per cent of the irrigation requirement with one lateral for each row of crop was 3.8 and treatment T6, 85 per cent of the irrigation requirement with one lateral in between two rows of crop was 3.9. Even though the yield for the treatment T5 was high, the benefit cost ratio stands high for treatment T6. The high value of benefit cost ratio for treatment T6 was due to the reduction in the quantity of material for drip irrigation system